The Power of Community Marketing: How Brands Are Building Loyal Audiences - Lesmana, Alvin (Jurnal Informatika Ekonomi Bisnis, 2025)
This study investigates the impact of community marketing on audience loyalty, focusing on the mediating roles of brand trust and customer engagement. Utilizing a quantitative research design, data were collected through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that community marketing has a significant direct effect on audience loyalty, while also exerting indirect influence through brand trust and customer engagement. Both mediators were found to significantly strengthen the relationship between community marketing and audience loyalty, with customer engagement showing a particularly strong mediating effect. These findings contribute to a deeper understanding of how community-oriented strategies foster trust, increase active participation, and ultimately build lasting consumer loyalty. The study provides theoretical and practical implications for marketers aiming to develop sustainable, relationship-based brand strategies in the digital era.